The Autoimmune-Associated Single Nucleotide Polymorphism Within PTPN22 Correlates With Clinical Outcome After Lung Transplantation - Budding, Kevin; van Setten, Jessica; van de Graaf, Eduard A.; van Rossum, Oliver A.; Kardol-Hoefnagel, Tineke; Kwakkel-van Erp, Johanna M.; Oudijk, Erik-Jan D.; Hack, C. Erik; Otten, Henderikus G. (Frontiers in Immunology, 2019)
Obstructive chronic lung allograft dysfunction (BOS) is the major limiting factor for lung transplantation (LTx) outcome. PTPN22 is described as the hallmark autoimmunity gene, and one specific single nucleotide polymorphism (SNP), rs2476601, is associated with multiple autoimmune diseases, impaired T cell regulation and autoantibody formation. Taking into consideration the contribution of autoimmunity to LTx outcome, we hypothesized that polymorphisms in the PTPN22 gene could be associated with BOS incidence. We selected six SNPs within PTPN22 and analyzed both patient and donor genotypes on BOS development post-LTx. A total of 144 patients and matched donors were included, and individual SNPs and haplotype configurations were analyzed. We found a significant association between patients carrying the heterozygous configuration of rs2476601 and a higher risk for BOS development (p=0.005, OR: 4.400, 95%CI: 1.563–12.390). Kaplan-Meier analysis showed that heterozygous patients exhibit a lower BOS-free survival compared to patients homozygous for rs2476601 (p=0.0047). One haplotype, which solely contained the heterozygous risk variant, was associated with BOS development (p=0.015, OR: 7.029, 95%CI: 1.352–36.543). Our results show that LTx patients heterozygous for rs2476601 are more susceptible for BOS development and indicate a deleterious effect of the autoimmune-related risk factor of PTPN22 in patients on LTx outcome.